Application of Magnetic Resonance Imaging and Magnetic Resonance Angiography as Diagnostic Measures for the First Attack of Suspected Cerebrovascular Diseases in Korea - Lee, Kunsei (Yonsei University College of Medicine, 2011)
PURPOSE: No precise data are available showing how magnetic resonance imaging (MRI) and magnetic resonance angiography (MRA) can be applied to diagnosis for the first attack of a suspected cerebrovascular disease in Korea. The purpose of this study was to evaluate the application level of MRI and MRA as diagnostic tools and the related factors to the use of these techniques. MATERIALS AND METHODS: This study used the health benefit claim data of 89,890 patients who were hospitalized for the first time due to suspected cerebrovascular disease in 2007 without having visited medical institutions as an outpatient or inpatient from 2003 to 2006. RESULTS: Of the 89,890 cases, 28.4% took both MRI and MRA, 10.7% took only MRI and 6.9% took only MRA. The related factors identified in the multivariate logistic regression analysis were gender, type of insurance, type of medical institution, type of department, duration of hospitalization, and type of disease. CONCLUSION: This study showed that the application level of MRI and MRA as diagnostic measures for the first attack of a suspected cerebrovascular diseases varied depending on several factors. It is necessary to study more accurate levels of computerized tomography (CT), computerized tomography angiography (CTA), MRI or MRA as measures to diagnose a first attack of suspected cerebrovascular disease.